The Association of the Levels of Perceived Stress With the Preferred Mode of Delivery in Primiparous Women - Soheila Nazeri; Leila Amini; Homa Sadeghi Avval Shahr; Shima Haghani; Hossein Heshmati (Iran University of Medical Sciences, 2022)
Background & Aims: This study aimed to investigate the relationship between perceived stress and the preferred mode of delivery in primiparous pregnant women in 2019.  Materials & Methods: The present study was a cross-sectional investigation in which the relationship between the perceived stress of primiparous women and their preferred mode of delivery was evaluated. The population in this study was all of the primiparous women attending the healthcare centers in Bandar Abbas in 2019, among which 230 women were sampled through a multi-stage sampling process. Data acquisition was performed via Cohen's Perceived Stress Questionnaire and a demographic and gynecological information checklist. Statistical analysis was performed using SPSS software v. 23 and Chi-square, Welch's t-test, Pearson's correlation test, and one-way and two-way analysis of variance with post-hoc. P<0.05 was considered significant.  Results: The Mean±SD age of the samples was 25.84±5.09, and the majority of participants were unemployed (86.9%), had high school education (50%), and had moderate economic status (66.1%), and preferred vaginal delivery as the mode of birthing (75.7%). The Mean±SD perceived stress score was 23.14±8.70. The results have shown that there is a statistically significant relationship between the perceived stress score and preferred mode of delivery (P=0.033), type of pregnancy (wanted/unwanted; P=0.029), and economic status (P=0.004). There was a statistically significant relationship between the preferred mode of delivery and the level of the education of the participants (P=0.043) and their spouses (P=0.005), the employment status of the participant (P=0.005), the number of years that the participants and their spouses were educated (P=0.001 and P=0.001). Conclusion: Women who experience this type of pregnancy require higher levels of social support. In addition, there is a need for proper educative programs that would inform couples of the benefits and harms of different delivery.